2019
DOI: 10.9734/aprj/2019/v2i430054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methanolic Extract of Corchorus olitorius Leaves on Hypoglycemic and Hypolipidaemic Activities in Albino Rats

Abstract: Aim: This study sought to investigate the hypoglycemic and hypolipidaemic effect of methanolic extract of Corchorus olitorius leaves in Albino rats. Methods: Fresh plants of C. olitorius were harvested from the Institute of Agricultural Research and Training, Ibadan. The leaves were dried and extracted using soxhlet apparatus and methanol as the solvent. The methanol was evaporated in a rotary evaporator at 35°C with a yield of 2.17 g which represents a percentage yield of 8.68%. Ten adult male albino ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 32 publications
4
29
1
Order By: Relevance
“…5) at p<0.05. This contradicts the findings of Airaodion et al [24] who reported a significant increase in the HDL-cholesterol concentration when animals were treated with methanolic extract of Corchorus olitorius leaves for 14 days. HDL-cholesterol is usually referred to as the 'good cholesterol' [26].…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…5) at p<0.05. This contradicts the findings of Airaodion et al [24] who reported a significant increase in the HDL-cholesterol concentration when animals were treated with methanolic extract of Corchorus olitorius leaves for 14 days. HDL-cholesterol is usually referred to as the 'good cholesterol' [26].…”
Section: Discussioncontrasting
confidence: 96%
“…The fasting blood sugar lowering effect of V. amygdalina leaves could also indicate that it possesses antidiabetic agents which could control hyperglycaemia. This is consistent with earlier reports that green leafy vegetables possess antidiabetic properties [24,35,36]. One therapeutic approach for treating early stage of diabetes is to decrease post-prandial hyperglycaemia.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations